Pengaruh Keterampilan Kebekerjaan dan Efikasi Diri Terhadap Kesiapan Kerja Siswa SMK Negeri 2 Gowa - Fitri; Ruslan; Anas Arfandi; Abdul Muis Mapalotteng; Alimuddin Sa'ban Miru (UNM Journal of Technology and Vocational, 2023)
The study aims to examine: (1) the influence of employability skills on the students’ work readiness at SMKN 2 Gowa; (2) the influence of self-efficacy on the students’ work readiness at SMKN 2 Gowa; and (3) the influence of employability skills and self-efficacy on the students’ work readiness t SMKN 2 Gowa. The type of research used is quantitative using the Ex-post Facto method. The research samples were 184 students of grade XII. Data collection techniques employed questionnaire, and documentation. Data were analyzed using descriptive statistical analysis, analysis prerequisite test, and hypothesis testing. The results of the study reveal that (1) there is an influence of employability skills on the students’ work readiness at SMKN 2 Gowa; (2) there is an influence of self-efficacy on the students’ work readiness at SMKN 2 Gowa; and (3) there is an influence of employability skills and self-efficacy collectively on the students’ work readiness at SMKN 2 Gowa.